1. ## simplifying the expression

Hello,

Can you please help me simplify this expression? I'd like to see what happens step by step

y = u*v'*w'+u*v'*w+u*v*w

' denotes compliment.
+ OR
* AND

2. What ideas have you had so far?

3. i'm getting stuck at this part:

y = u*((v'*w')+(v'*w)+(v*w))

what can I do next?

4. I have not tried to help here because it is almost impossible to read the question.
Is it to simplify $\displaystyle \left( {U \wedge \neg V \wedge \neg W} \right) \vee \left( {U \wedge \neg V \wedge W} \right) \vee \left( {U \wedge V \wedge W} \right)~?$

Please learn to post in symbols: You can use LaTeX tags.

5. More standard notation would omit the *'s and use implied multiplication thus:

u((v' w') + (v' w) + (v w)). The first two terms inside the parentheses there have a term in common. You could factor that, I think. What does that give you?

6. sorry, yea that's correct.

7. thats where I was having problems with...

does it factor to this???

u((v' ((w' + w) + (v w))))

8. I think I sorta get it...

(w' + w) cancels each other

(v' + v w) expands to

(v' + v)(v'+w) ---> (v' + w)

therefore i'm left with

u(v' + w) as my answer...

9. Looks good to me!